2021
DOI: 10.1111/hae.14302
|View full text |Cite
|
Sign up to set email alerts
|

Clinical attributes and treatment characteristics are associated with work productivity and activity impairment in people with severe haemophilia A

Abstract: Introduction Few studies have examined the real‐world impact of haemophilia on daily activities and work productivity in people with severe haemophilia A (PWSHA). Aim To determine clinical attributes and treatment characteristics associated with impairment in daily activities and work among PWSHA using the patient‐reported Work Productivity and Activity Impairment‐General Health Questionnaire (WPAI‐GH). Methods PWSHA were asked to complete the WPAI‐GH as part of the Cost of Haemophilia in Europe: A Socioeconom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 30 publications
0
16
2
Order By: Relevance
“…For most, it requires a high‐level of engagement by the patient and the healthcare staff. In another cross‐sectional study, the presence of a reported target joint was associated with a poorer quality of life as shown by a lower mean EQ‐5D index score (.731 vs. .875) 14 . In the current study, haemophilia‐related distress was not independently associated with the presence of a target joint.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…For most, it requires a high‐level of engagement by the patient and the healthcare staff. In another cross‐sectional study, the presence of a reported target joint was associated with a poorer quality of life as shown by a lower mean EQ‐5D index score (.731 vs. .875) 14 . In the current study, haemophilia‐related distress was not independently associated with the presence of a target joint.…”
Section: Discussioncontrasting
confidence: 47%
“…In another cross-sectional study, the presence of a reported target joint was associated with a poorer quality of life as shown by a lower mean EQ-5D index score (.731 vs. .875). 14 In the current study, haemophilia-related distress was not independently associated with the presence of a target joint. However, those with public insurance had a 4.86 greater odds of having a target joint than those with private insurance, after controlling for other variables.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“… 16 Among persons with severe hemophilia A in five European countries, lifelong prophylaxis and high therapy adherence led to reduced activity impairment and work productivity loss, whereas frequent bleeds and pain were associated with increased activity impairment and work productivity loss. 17 …”
Section: Introductionmentioning
confidence: 99%
“…16 Among persons with severe hemophilia A in five European countries, lifelong prophylaxis and high therapy adherence led to reduced activity impairment and work productivity loss, whereas frequent bleeds and pain were associated with increased activity impairment and work productivity loss. 17 Few studies have examined the "gap" in socioeconomic participation between persons with different severities of hemophilia and the general population. Furthermore, participation outcomes are often not reported in a standardized manner (i.e., Results: Data from 906 adults and children were analyzed.…”
Section: Introductionmentioning
confidence: 99%